A COMPARATIVE CLINICAL STUDY TO EVALUATE THE EFFECT OF TANDULIYAKA IN GARBHINI PANDU W.S.R. TO ANAEMIA DURING PREGNANCY - Ritu, *Singh; D.C, Singh; Pravesh, Tomar (International Journal of Ayurveda and Pharma Research, 2017)
Under-nutrition and micronutrient deficiencies are widespread and affect mainly women and children. To address these problems, increased consumption of leafy vegetables is promoted as sources of both micronutrients and bio-active compounds. Widely promoted leafy vegetables include Amaranthus sp., Species of this genus are used as pseudo-cereals in Europe and America, and are mostly planted as vegetables in Africa. Amaranthus has been rediscovered as a promising food crop mainly due to its resistance to heat, drought, diseases and pests, and the high nutritional value of both seeds and leaves. Leaves are rich in proteins and micronutrients such as iron, calcium, zinc, vitamin C and vitamin A. Pregnancy induces some physiological changes that often confuse the diagnosis of several disorders and the assessment of the suitable treatments. This is especially true in case of anaemia. The World Health Organization estimates that 58% of pregnant women in developing countries are anaemic. The two most common causes of anaemia during pregnancy are iron deficiency and acute blood loss. Iron deficiency anaemia is the most common nutritional disorder in the world that affects particularly women of reproductive age. In the present study Amaranthus capsules showed significant improvement in terms of subjective parameters like Panduta, Hrid-drava, Shrama, Swasa, Aruchi, as well as objective parameters like Hb%, MCV, PCV, RBC etc. This study has revealed that Amaranthus capsules provided statistically significant improvement in the cardinal features of Garbhinipandu as well as it has showed good effect on jatharagni and nourishment of pregnant women and foetus without any side-effects, due to its properties like deepana, pachana, and high nutritional value.